LOGISTICS ACTIVITIES OF MAINTENANCE PROCESSES - Telek, Péter (Advanced Logistic Systems - Theory and Practice, 2023)
The maintenance process, as a part of the operation of manufacturing systems, is also developing, following the changes in the production area. One of the most important characterization of this changing is that the maintenance appears as an independent service element of the production process. Because of this tendency maintenance logistics also has to be changed, which requires new elements, relations and new approaches. Main objective of our research is to uncover the relations among the efficiency of the maintenance processes and the material handling parameters. In this paper we summarise the development of the maintenance logistics and give an overview about the actual handling tasks, which must be solved.